2020
DOI: 10.1155/2020/1859431
|View full text |Cite
|
Sign up to set email alerts
|

Role of Astrocytic Dysfunction in the Pathogenesis of Parkinson’s Disease Animal Models from a Molecular Signaling Perspective

Abstract: Despite the fact that astrocytes are the most abundant glial cells, critical for brain function, few studies have dealt with their possible role in neurodegenerative diseases like Parkinson's disease (PD). This article explores relevant evidence on the involvement of astrocytes in experimental PD neurodegeneration from a molecular signaling perspective. For a long time, astrocytic proliferation was merely considered a byproduct of neuroinflammation, but by the time being, it is clear that astrocytic dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 94 publications
0
13
0
Order By: Relevance
“…In the conditional calcium/calmodulin-dependent protein kinase II alpha model, there is an association between decreased hippocampal neurogenesis and memory retention (Nuber et al, 2008). Additional roles of glia cell NP has also been described by Udovin et al (2020), where the Wnt-1 receptor (pathway originally involved in nearby cell-cell communication) also regulates several NP mechanisms (including neuron survival, synapse plasticity, and neurogenesis) favoring neuron survival and viability (Udovin et al, 2020).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…In the conditional calcium/calmodulin-dependent protein kinase II alpha model, there is an association between decreased hippocampal neurogenesis and memory retention (Nuber et al, 2008). Additional roles of glia cell NP has also been described by Udovin et al (2020), where the Wnt-1 receptor (pathway originally involved in nearby cell-cell communication) also regulates several NP mechanisms (including neuron survival, synapse plasticity, and neurogenesis) favoring neuron survival and viability (Udovin et al, 2020).…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Normal human NHAs are the most abundant cell types in the central nervous system, providing nutritional support for neurons and maintaining the function of the central nervous system [14]. Studies have shown that the function of NHAs is regulated by microglia, microorganisms, and…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular mechanisms shape the response of the astrocytes to distinct neurodegenerative disorders, such as for example AD [133], ALS [12], HD [134], and PD [135].…”
Section: Shared Pathways Of Astrocyte Dysfunction In Neurodegenerative Diseasesmentioning
confidence: 99%